2020
DOI: 10.3390/nano10122566
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dot-TiO2 Photonic Crystal Films for Photocatalytic Applications

Abstract: Photonic crystal structuring has emerged as an advanced method to enhance solar light harvesting by metal oxide photocatalysts along with rational compositional modifications of the materials’ properties. In this work, surface functionalization of TiO2 photonic crystals by blue luminescent graphene quantum dots (GQDs), n–π* band at ca. 350 nm, is demonstrated as a facile, environmental benign method to promote photocatalytic activity by the combination of slow photon-assisted light trapping with GQD-TiO2 inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The hexagonally ordered macropores of the inverse opals structure were interconnected through smaller ones (dark areas within the large spherical voids) that form after calcination at the contact points of neighboring polymer spheres facilitating mass transfer in the pore network. Their mean diameter ( D ) determined by SEM, increased proportionally to the colloidal sphere size ( Table 1 ), while the obtained values were about 60% smaller than those of the templating spheres because of the persistent volume contraction of crystalline metal oxide inverse opals [ 33 , 60 ]. Cross-section SEM images revealed that the thickness of the inverse opal films was approximately 4 μm ( Figure 1 e), while that for the P25 film was approximately 2.2 μm ( Figure 1 f).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hexagonally ordered macropores of the inverse opals structure were interconnected through smaller ones (dark areas within the large spherical voids) that form after calcination at the contact points of neighboring polymer spheres facilitating mass transfer in the pore network. Their mean diameter ( D ) determined by SEM, increased proportionally to the colloidal sphere size ( Table 1 ), while the obtained values were about 60% smaller than those of the templating spheres because of the persistent volume contraction of crystalline metal oxide inverse opals [ 33 , 60 ]. Cross-section SEM images revealed that the thickness of the inverse opal films was approximately 4 μm ( Figure 1 e), while that for the P25 film was approximately 2.2 μm ( Figure 1 f).…”
Section: Resultsmentioning
confidence: 99%
“…Films of 2 cm 2 area were initially stirred in vials containing 3 mL of 30 μΜ SA aqueous solution for 30 min under dark in order to reach adsorption-desorption equilibrium. The solution pH was fixed at 3 by dilute HCL in order to enhance SA adsorption on the TiO 2 films [ 33 ]. A 150 W Xe lamp was used as a UV–Vis light source along with a heat-reflective mirror (20CLVS-3, Newport, Irvine, CA, USA), while visible light was selected by a 400 nm cutoff filter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the composites of PCs with graphene-based materials (G, GO, rGO) have been explored for numerous applications, such as switch [47], electronic and optoelectronic devices [48][49][50][51], sensors [52,53], surface-enhanced Raman scattering (SERS) [54], and photocatalysis [47,55,56], as exemplary shown in Table 1.…”
Section: Graphene-based Photonic Crystalsmentioning
confidence: 99%
“…The fabrications of graphene-based PCs, where graphene-like materials (GO/rGO) act as co-catalysts, has been mostly carried out by immersing/dipping the IO PC into GO colloidal suspension with subsequent post-thermal treatment (calcination) [55,68,69,71]. On the other hand, the formation of graphene-like materials as the backbone material of IO PC requires at least three-step procedure i.e., (i) preparation of template (opal), (ii) infiltration of opal with targeted material, and (iii) the removal of sacrificial template.…”
Section: Graphene-based Photonic Crystalsmentioning
confidence: 99%